2004
DOI: 10.1590/s0100-204x2004000300003
|View full text |Cite
|
Sign up to set email alerts
|

Efeito de banhos terapêuticos com formalina sobre indicadores de estresse em tambaqui

Abstract: Resumo -A formalina tem sido usada no controle de doenças parasitárias, porém existem poucas informações sobre o efeito secundário desse produto sobre os peixes. O objetivo deste trabalho foi avaliar o efeito de concentrações terapêuticas de formalina na homeostase de tambaqui (Colossoma macropomum Cuvier 1818) por meio de índices fisiológicos. Os banhos terapêuticos foram realizados em tanques de 100 L, com soluções de formalina a 0, 100, 150, 200 e 250 mg/L, em tempos de exposição de 0, 30, 60 e 120 minutos;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…Besides the ions, hematological parameters in this study were similar to that found in non-supplemented fish and are in agreement with previous studies for C. macropomum (Chagas et al, 2003;Araújo et al, 2004;Tavares-Dias, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Besides the ions, hematological parameters in this study were similar to that found in non-supplemented fish and are in agreement with previous studies for C. macropomum (Chagas et al, 2003;Araújo et al, 2004;Tavares-Dias, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Therapeutic bathes (Hashimoto et al, 2016;Malheiros et al, 2016;Soares et al, 2016) and medicated diet (Kim and Choi, 1998;Forwood et al, 2013;Militz et al, 2013) have been used to control monogenean infestations. The most used treatments for monogenean parasites are formalin, potassium permanganate, sodium chloride, acetic acid, hydrogen peroxide (Kabata, 1985;Thatcher, 1991;Fajer-Ávila et al, 2003;Araújo et al, 2004;Bowker et al, 2012;Chagas et al, 2012;Farmer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Tertiary responses affect the animals' organism, compromising their growth, their resistance to diseases and their reproductive success (Wedemeyer, 1997;Wendelaar Bonga, 1997;Jorgensen and Jørgensen and Buchmann, 2007). Glucose and plasma cortisol are common indicators of stress in fish (Omoregie et al, 1994;Jung et al, 2003;Araújo et al, 2004;Jorgensen and Jørgensen and Buchmann, 2007).…”
Section: Parametersmentioning
confidence: 99%
“…Similarly, cortisol levels increased in fish exposed to 44, 55 and 66 mg L − 1 formalin whereas calcium levels decreased. Plasma glucose levels also increased in carps (Kakuta et al, 1991) and formalin-exposed tilapias (Omoregie et al, 1994), as well as in Colossoma macropomum exposed to 100, 150, 200 and 250 mg L − 1 formalin, during different exposure times (Araújo et al, 2004). In contrast, Jung et al (2003) studied the effects of formalin 100, 212 and 300 mg L − 1 on Paralichthys olivaceusis for 3 h, and they did not observe changes in plasma glucose levels.…”
Section: Parametersmentioning
confidence: 99%
“…Researches evaluating fish stress with Brazilian species were made with matrinxã ( Brycon cephalus ) (Carneiro and Urbinati, ; Ide et al., ; Rocha et al., ), tambaqui ( Colossoma macropomum ) (Araújo et al., ), pirarucu ( Arapaimas gigas ) (Brandão et al., ; Gomes, ) and jundiá ( Randia quelen ) (Barcellos et al., ). Barton () considered stress as a set of non‐specific responses of the organism to situations that threaten fish homoeostasis.…”
Section: Introductionmentioning
confidence: 99%